High-temperature-resistant flexible plugging material and preparation method thereof

By combining polysiloxane matrix and interface compatibilizer, a high-temperature resistant flexible sealing material was prepared, which solved the problem of toxic gases generated by existing materials at high temperatures and poor structural strength, and achieved efficient heat insulation , fireproof, waterproof and good combination with concrete.

CN119490753APending Publication Date: 2025-02-21BENGBU ESTONE POLYMER COMPOSITES CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411600722.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing flexible organic sealing materials produce toxic gases at high temperatures, have poor structural strength, cannot effectively isolate flames, and have poor compatibility with concrete and other materials, resulting in insufficient binding force during construction, and may appear, affecting the fire protection effect.

Method used

Using polysiloxane matrix combined with interface compatibility agent, combined with heat insulation filler, flame retardant filler, porcelain filler and filler, high temperature-resistant flexible sealing materials are prepared through kneading and screw discharge processes, and the material and concrete surface are improved. the bonding power.

Benefits of technology

The sealing material is achieved without toxicity, heat insulation, fireproof, waterproof and airtight at high temperatures. At the same time, the bonding force between the material and concrete is improved, preventing falling off and gap formation, and enhancing the fireproof and isolation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490753A_ABST
    Figure CN119490753A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant flexible plugging material and a preparation method thereof, and relates to the technical field of plugging materials, the high-temperature-resistant flexible plugging material comprises the following raw materials by weight: 100 parts of a polysiloxane matrix, 5-150 parts of a thermal insulation filler, 10-150 parts of a ceramic forming filler, 0-150 parts of a flame retardant filler, 0-200 parts of a filler, and 1-20 parts of an interfacial compatibilizer; the modified polysiloxane matrix containing the anion group is used as an interface compatilizer of the plugging material and materials such as concrete, the surface binding force of the plugging material and the materials such as the concrete can be improved, construction is easy, and the plugging material does not fall off for a long time after construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plugging materials, and in particular to a high-temperature resistant flexible plugging material and a preparation method thereof. Background Art

[0002] Flexible organic sealing material is a non-solidifying fireproof sealing material used in industrial and mining enterprises, high-rise buildings, electric power, post and telecommunications, etc. to seal various penetrating objects such as openings formed when cables and pipes pass through wall panels or floor slabs, as well as building gaps, to prevent the flame from spreading from the holes to adjacent rooms in the event of a fire.

[0003] Traditional flexible organic plugging materials are made by mixing liquid chlorinated paraffin and porcelain clay powder in a certain proportion, which can meet the requirements of national standard GB 23864-2009 for combustion performance, apparent density, corrosion resistance, water resistance, moisture and heat resistance, and cyclic freeze-thaw resistance. However, the use of chlorinated paraffin as a base material has the problem of drying and hardening in winter and softening and flowing in summer. The most important thing is that it will produce toxic gases containing halogens when exposed to high temperatures, which will endanger the lives of on-site personnel in the event of a fire. In addition, the product strength of the material after high-temperature decomposition is poor, and the overall structure is prone to collapse. The flame spreads to the adjacent room along the hole, and it cannot play a role in fire isolation. This is also the new smoke toxicity and airtightness requirements for fireproof plugging materials added by national standard GB 23864-2023.

[0004] In order to meet the new requirements, the use of organic silicon materials in combination with other ceramic powders, heat insulation materials, high temperature resistant materials and other functional fillers to prepare organic silicon-based flexible organic plugging materials is one of the best solutions at present. The advantages of organic silicon materials are that they are non-toxic and tasteless at room temperature, have good sealing properties, good elasticity, do not absorb moisture, are resistant to high and low temperatures, are resistant to aging, have excellent electrical insulation properties and good processing properties, and are basically non-toxic and do not produce halogen-containing substances when subjected to high temperature burning. The decomposition product of organic silicon materials is silicon dioxide, which can form a complete ceramic-like hard shell when combined with other functional fillers when subjected to high temperature burning, thereby isolating the external flame.

[0005] Patent CN 116814079A discloses a method for preparing a non-solidifying fireproof and moisture-proof silica gel mud. The polysiloxane matrix, refractory filler, flame retardant, cross-linking agent, microencapsulated platinum catalyst, modifier and stabilizer are subjected to processes such as kneading and screw extrusion to prepare the non-solidifying fireproof and moisture-proof silica gel mud. The non-solidifying fireproof and moisture-proof silica gel mud has excellent properties such as halogen-free flame retardancy, heat insulation, fireproof and moisture-proof, soft in all seasons, no cracking, no oil flow, ceramicization, and cross-linking. It can maintain its original shape when a fire occurs, and no powdering, dripping, etc. will occur.

[0006] Patent CN 118146634A discloses a fireproof blocking material, which includes the following components: hydroxy-terminated phenyl silicone oil, α,ω-dihydroxy polydimethylsiloxane, white carbon black, synergistic flame retardant, flame retardant filler, cross-linking agent, coupling agent and catalyst. The fireproof blocking material has good fire resistance, sound insulation, smoke insulation and air tightness, and still has good mechanical strength and elasticity at high temperature.

[0007] However, due to the poor compatibility between organic plugging materials and inorganic concrete materials, the bonding force at the interface where the two are in contact is poor, and the material is not easy to construct. At the same time, in order to maintain good construction performance, small molecular weight organic liquid components are generally added to the plugging materials to increase their plasticity, such as liquid chlorinated paraffin, silicone oil, etc. As the small molecular substances in the plugging materials evaporate, their volume shrinks. When the room temperature curing silicone plugging materials slowly solidify, their structure changes and their volume also slowly shrinks. Due to cost reasons, the inorganic powder component content of general plugging materials is high and the specific gravity is large. Under the premise of maintaining good plasticity, the plugging materials will slowly deform due to their own weight. Based on the above reasons, the plugging materials may produce gaps at the interface after construction, and cannot play the role of isolating flames and toxic gases when a fire occurs. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a high temperature resistant flexible sealing material and a preparation method thereof, wherein the obtained sealing material has the properties of anti-falling, high temperature resistance, aging resistance, heat insulation, fire resistance, waterproofness, non-toxicity and good air tightness.

[0009] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0010] One of the purposes of the present invention is to provide a high temperature resistant flexible plugging material, comprising the following raw materials in parts by weight:

[0011]

[0012]

[0013] The second object of the present invention is to provide a method for preparing a high temperature resistant flexible plugging material, comprising the following steps:

[0014] (1) putting a polysiloxane matrix and an interfacial compatibilizer into a kneader, then adding a heat insulating filler, a flame retardant filler, a ceramic filler and a filler, kneading, and cooling to obtain a base rubber;

[0015] (2) The base rubber is discharged through a screw and cut into suitable lengths to obtain a high temperature resistant flexible sealing material.

[0016] The beneficial effects of the present invention are:

[0017] 1. The present invention uses fly ash or floating beads with extremely high compressive strength and insulation performance as thermal insulation filler, which can maintain the integrity of the structure during the processing of the plugging material. The prepared plugging material can maintain a high thermal insulation effect while maintaining the inherent high temperature resistance, aging resistance, air tightness, fire resistance, waterproofness, non-toxicity and other properties of the silicone material.

[0018] 2. The surfaces of the particles of components in materials such as concrete, such as calcium sulfonate, tricalcium aluminate, tetracalcium ferroaluminate, monosulfur calcium sulfoaluminate, potassium feldspar, etc., are positively charged. The present invention uses a modified polysiloxane matrix containing anionic groups as an interface compatibilizer between the plugging material and materials such as concrete, wherein the negatively charged anionic groups can form electrostatic adsorption with the surface of the particles with positive charge, thereby improving the bonding force between the plugging material and the surface of materials such as concrete, making it easy to construct and not falling off for a long time after construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The diagram is a failure mode diagram of the plugging materials prepared in Example 1, Comparative Example 1, Comparative Example 5 and Comparative Example 6 when testing their bonding strength with the concrete surface. DETAILED DESCRIPTION

[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0021] The present invention provides a high temperature resistant flexible plugging material, comprising the following raw materials in parts by weight:

[0022]

[0023]

[0024] Preferably, the high temperature resistant flexible plugging material comprises the following raw materials in parts by weight:

[0025]

[0026] In the present invention, the polysiloxane matrix is ​​compounded by silicone oil (liquid polysiloxane) and silicone rubber (solid polysiloxane) in a weight ratio of 1: (0.1-10). Preferably, the polysiloxane matrix is ​​compounded by silicone oil and silicone rubber in a weight ratio of 1: (0.5-2).

[0027] Furthermore, the silicone oil includes but is not limited to one or more of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, hydroxy silicone oil, vinyl silicone oil, amino silicone oil, hydrogen silicone oil, fluorosilicone oil, and hydroxypropyl silicone oil. The viscosity of the silicone oil is 5 to 200,000 mm 2 / s, preferably 200~10000mm 2 / s.

[0028] Furthermore, the silicone rubber includes but is not limited to one or more of methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, fluorosilicone rubber, and nitrile silicone rubber. The molecular weight of the silicone rubber is 150,000 to 1,000,000, preferably 400,000 to 800,000.

[0029] In the present invention, the thermal insulation filler includes but is not limited to one or more of expanded perlite, expanded vermiculite, fly ash, floating beads, hollow glass microspheres, diatomaceous earth, zeolite powder, hollow silica microspheres, and hollow alumina microspheres.

[0030] In the present invention, the ceramic-forming filler includes, but is not limited to, one or more of low-melting-point glass powder, zinc oxide, calcium oxide, zinc borate, calcium borate, mica powder, wollastonite powder, and palygorskite powder.

[0031] In the present invention, the flame retardant filler includes but is not limited to one or more of magnesium hydroxide, aluminum hydroxide, basic magnesium carbonate, ammonium polyphosphate, and microcapsule composite flame retardant.

[0032] In the present invention, the filler includes but is not limited to one or more of calcium carbonate, quartz powder, calcium sulfate, kaolin, talc, montmorillonite and attapulgite.

[0033] In the present invention, the interfacial compatibilizer is an anionic surfactant, including but not limited to one or more of carboxylic acid and its salt anionic surfactants, sulfonate anionic surfactants, sulfate anionic surfactants, and phosphate anionic surfactants. Among them, the carboxylic acid and its salt anionic surfactants include but are not limited to one or more of fatty acids such as oleic acid, lauric acid, stearic acid, and their potassium salts, sodium salts, ammonium salts, and triethanolammonium salts. The sulfonate anionic surfactants include but are not limited to succinic acid monooctadecylamide sulfonic acid sodium salt, dodecylbenzenesulfonic acid, sodium dodecyldiphenyl ether disulfonate, allyloxy hydroxypropane sulfonic acid sodium salt, methacrylic acid hydroxypropane sulfonate sodium salt, 2-acrylamido-2-methylpropane sulfonic acid sodium salt, allyloxy sodium sulfonate, sodium vinyl sulfonate, melamine sulfonate formaldehyde condensate, β-naphthalene sulfonate formaldehyde condensate, and lignin sulfonate. The sulfate anionic surfactants include, but are not limited to, one or more of sodium dodecyl sulfate, sodium laureth sulfate, allyloxy nonylphenol polyoxyethylene (10) ether ammonium sulfate, nonylphenol polyoxyethylene (4) ether ammonium sulfate, nonylphenol polyoxyethylene (4) ether sodium sulfate, alkyl alcohol polyoxyethylene (1-4) ether sodium sulfate, alkyl alcohol polyoxyethylene (3) ether ammonium sulfate, n-decyl sodium sulfate, isomeric tridecanol polyoxyethylene (5) ether ammonium sulfate. The phosphate anionic surfactants include, but are not limited to, one or more of polyoxyethylene dodecyl ether phosphate, potassium cetyl alcohol phosphate, and allyloxy nonylphenol polyoxyethylene (10) ether monophosphate.

[0034] In addition to the anionic surfactant, the interfacial compatibilizer also includes but is not limited to one or more of the anionic groups grafted modified organic polysiloxanes such as carboxylic acid (and its salt) group, sulfonic acid (and its salt) group, sulfate (and its salt) group, phosphate (and its salt) group, etc.

[0035] The present invention also provides a method for preparing a high temperature resistant flexible plugging material, comprising the following steps:

[0036] (1) putting a polysiloxane matrix and an interfacial compatibilizer into a kneader, then adding a heat insulating filler, a flame retardant filler, a ceramic filler and a filler, kneading, and cooling to obtain a base rubber;

[0037] (2) The base rubber is discharged through a screw and cut into suitable lengths to obtain a high temperature resistant flexible sealing material.

[0038] Furthermore, the kneading frequency is 43-47 Hz, the temperature is 30-200° C., and the time is 0.5-4 h.

[0039] Example 1

[0040] By weight, 50 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 50 parts of a viscosity of 500 mm2 / s of vinyl silicone oil and 10 parts of stearic acid are put into a kneader, and then 50 parts of fly ash, 80 parts of wollastonite powder, 50 parts of aluminum hydroxide and 50 parts of nano calcium carbonate are weighed and added into the kneader. The kneading frequency is set to 45 Hz and the kneading temperature is set to 90°C. After kneading for 1 hour, the temperature is cooled to room temperature to obtain a base rubber. The base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0041] Example 2

[0042] By weight, 65 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 35 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil and 10 parts of sodium dodecyl diphenyl ether disulfonate are put into a kneader, and then 30 parts of fly ash, 30 parts of low-melting point glass powder (D245), 50 parts of ammonium polyphosphate, and 80 parts of kaolin are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 120°C, and after kneading for 2 hours, it is cooled to room temperature to obtain a base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0043] Example 3

[0044] By weight, 20 parts of methyl vinyl silicone rubber with a molecular weight of 800,000, 80 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil and 10 parts of sodium lauryl polyether sulfate are put into a kneader, and then 30 parts of floating beads, 50 parts of zinc borate, 70 parts of magnesium hydroxide and 50 parts of montmorillonite are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 150°C, and after kneading for 1 hour, the temperature is cooled to room temperature to obtain a base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0045] Example 4

[0046] By weight, 50 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 50 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil and 8 parts of potassium cetyl phosphate are put into a kneader, and then 70 parts of diatomaceous earth, 50 parts of calcium borate and 120 parts of nano calcium carbonate are weighed and added to the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is 80°C, and after kneading for 1.5 hours, it is cooled to room temperature to obtain a base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0047] Comparative Example 1

[0048] The method of Example 1 was followed, except that the anionic surfactant stearic acid was not added as an interfacial compatibilizer.

[0049] By weight, 50 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 50 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil is put into the kneader, and then 50 parts of fly ash, 80 parts of wollastonite powder, 50 parts of aluminum hydroxide and 50 parts of nano calcium carbonate are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 90°C, and after kneading for 1 hour, it is cooled to room temperature to obtain the base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain the plugging material.

[0050] Comparative Example 2

[0051] The method of Example 2 was followed, except that the anionic surfactant sodium dodecyl diphenyl ether disulfonate was not added as an interfacial compatibilizer.

[0052] By weight, 65 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 35 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil is put into the kneader, and then 30 parts of fly ash, 30 parts of low-melting point glass powder (D245), 50 parts of ammonium polyphosphate and 80 parts of kaolin are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 120°C, and after kneading for 2 hours, it is cooled to room temperature to obtain the base glue; the base glue is discharged through a screw and cut into suitable lengths to obtain the plugging material.

[0053] Comparative Example 3

[0054] The method of Example 3 was followed, except that the anionic surfactant sodium lauryl polyether sulfate was not added as an interfacial compatibilizer.

[0055] By weight, 20 parts of methyl vinyl silicone rubber with a molecular weight of 800,000, 80 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil is put into the kneader, and then 30 parts of floating beads, 50 parts of zinc borate, 70 parts of magnesium hydroxide and 50 parts of montmorillonite are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is 150°C, and after kneading for 1 hour, the temperature is cooled to room temperature to obtain the base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0056] Comparative Example 4

[0057] The method of Example 4 was followed, except that the anionic surfactant potassium cetyl phosphate was not added as an interfacial compatibilizer.

[0058] By weight, 50 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 50 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil is put into the kneader, and then 70 parts of diatomaceous earth, 50 parts of calcium borate and 120 parts of nano calcium carbonate are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 80°C, and after kneading for 1.5 hours, it is cooled to room temperature to obtain the base glue; the base glue is discharged by a screw and cut into suitable lengths to obtain the plugging material.

[0059] Comparative Example 5

[0060] The method of Example 1 was followed, except that a cationic surfactant, cetyltrimethylammonium bromide, was added as an interfacial compatibilizer.

[0061] By weight, 50 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 50 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil and 10 parts of hexadecyltrimethylammonium bromide are put into a kneader, and then 50 parts of fly ash, 80 parts of wollastonite powder, 50 parts of aluminum hydroxide and 50 parts of nano calcium carbonate are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 90°C, and after kneading for 1 hour, it is cooled to room temperature to obtain a base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0062] Comparative Example 6

[0063] The method of Example 1 is followed, except that a nonionic surfactant nonylphenol polyoxyethylene ether is added as an interfacial compatibilizer.

[0064] By weight, 50 parts of methyl vinyl silicone rubber with a molecular weight of 600,000, 50 parts of a viscosity of 500 mm 2 / s of vinyl silicone oil and 10 parts of nonylphenol polyoxyethylene ether are put into a kneader, and then 50 parts of fly ash, 80 parts of wollastonite powder, 50 parts of aluminum hydroxide and 50 parts of nano calcium carbonate are weighed and added into the kneader, the kneading frequency is set to 45 Hz, the kneading temperature is set to 90°C, and after kneading for 1 hour, it is cooled to room temperature to obtain a base rubber; the base rubber is discharged through a screw and cut into suitable lengths to obtain a plugging material.

[0065] The concrete surface bonding strength test was performed on the plugging materials prepared in the above examples and comparative examples:

[0066] C30 concrete is made into a circular device with a thickness of 10mm and a diameter of 40mm. The center of the circle has a vertical ordinary carbon structural steel plate as a clamping part. This circular device needs to be naturally cured for 7 days. The two circular concrete devices are clamped on the upper and lower clamps of the universal testing machine respectively, and the two circular devices are kept parallel. 20g of sealing material is placed between the two devices. After loading at a fixed load of 100N for 5 minutes, the edge overflow glue is removed. The cantilever movement speed of the universal testing machine is set to 5mm / min, and the maximum force of the test material combined with the concrete surface is tested. The test results are shown in Table 1.

[0067] Table 1

[0068] Maximum force / N Destruction Mode Maximum force / N Destruction Mode Example 1 33.49 Cohesive failure Comparative Example 2 21.44 Interface damage Example 2 39.63 Cohesive failure Comparative Example 3 19.21 Interface damage Example 3 35.18 Cohesive failure Comparative Example 4 15.78 Interface damage Example 4 38.92 Cohesive failure Comparative Example 5 12.36 Interface damage Comparative Example 1 14.47 Interface damage Comparative Example 6 22.47 Interface damage

[0069] It can be seen from Table 1 that the addition of anionic surfactant as an interface compatibility agent between the plugging material and the concrete surface can significantly improve the bonding force between the plugging material and the concrete, thereby enhancing the anti-falling performance of the plugging material.

[0070] Depend on Figure 1 It can be seen that in the process of testing the bonding strength between the sealing material and the concrete block, the sealing material in Example 1 is destroyed by itself, while Comparative Examples 1, 5 and 6 are separated from the interface between the sealing material and the concrete block. This shows that adding anionic surfactant as an interfacial compatibilizer can improve the bonding strength between the sealing material and the concrete.

[0071] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A high temperature resistant flexible plugging material, characterized in that: The invention comprises the following raw materials in parts by weight:

2. The high temperature resistant flexible plugging material according to claim 1, characterized in that: The high temperature resistant flexible plugging material comprises the following raw materials in parts by weight:

3. The high temperature resistant flexible plugging material according to claim 1 or 2, characterized in that: The polysiloxane matrix is ​​obtained by compounding silicone oil and silicone rubber in a weight ratio of 1:(0.1-10); preferably, the polysiloxane matrix is ​​obtained by compounding silicone oil and silicone rubber in a weight ratio of 1:(0.5-2).

4. The high temperature resistant flexible plugging material according to claim 3, characterized in that: The silicone oil is one or more of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, hydroxy silicone oil, vinyl silicone oil, amino silicone oil, hydrogen silicone oil, fluorosilicone oil, and hydroxypropyl silicone oil; the viscosity of the silicone oil is 5 to 200,000 mm 2 / s, preferably 200~10000mm 2 / s.

5. The high temperature resistant flexible plugging material according to claim 3, characterized in that: The silicone rubber raw rubber is one or more of methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, fluorosilicone rubber, and nitrile silicone rubber; the molecular weight of the silicone rubber raw rubber is 150,000 to 1,000,000, preferably 400,000 to 800,000.

6. The high temperature resistant flexible plugging material according to claim 1 or 2, characterized in that: The heat-insulating filler is one or more of expanded perlite, expanded vermiculite, fly ash, floating beads, hollow glass microspheres, diatomaceous earth, zeolite powder, hollow silica microspheres, and hollow alumina microspheres; Preferably, the ceramic-forming filler is one or more of low-melting-point glass powder, zinc oxide, calcium oxide, zinc borate, calcium borate, mica powder, wollastonite powder, and palygorskite powder; Preferably, the flame retardant filler is one or more of magnesium hydroxide, aluminum hydroxide, basic magnesium carbonate, ammonium polyphosphate, and microcapsule composite flame retardant; Preferably, the filler is one or more of calcium carbonate, quartz powder, calcium sulfate, kaolin, talc, montmorillonite and attapulgite.

7. The high temperature resistant flexible plugging material according to claim 1 or 2, characterized in that: The interfacial compatibilizer is an anionic surfactant; Preferably, the anionic surfactant is one or more of carboxylic acid and its salt anionic surfactants, sulfonate anionic surfactants, sulfate anionic surfactants, and phosphate anionic surfactants.

8. The high temperature resistant flexible plugging material according to claim 1 or 2, characterized in that: The interfacial compatibilizer is one or more of carboxylic acid (and its salt) groups, sulfonic acid (and its salt) groups, sulfate (and its salt) groups, and phosphate (and its salt) groups graft-modified organic polysiloxanes.

9. The method for preparing the high temperature resistant flexible plugging material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) putting a polysiloxane matrix and an interfacial compatibilizer into a kneader, then adding a heat insulating filler, a flame retardant filler, a ceramic filler and a filler, kneading, and cooling to obtain a base rubber; (2) The base rubber is discharged through a screw and cut into suitable lengths to obtain a high temperature resistant flexible sealing material.

10. The method for preparing the high temperature resistant flexible plugging material according to claim 9, characterized in that: The kneading frequency is 43-47 Hz, the temperature is 30-200° C., and the time is 0.5-4 h.

Citation Information

Patent Citations

  • Capillary tube-guided in-situ plugging cement-based composite material and use method thereof

    CN115028412A

  • Application of polyether modified organic silicon penetrant to preparation of organic silicon modified penetration enhancer

    CN115073747A

  • Silicon-containing anionic surfactant as well as preparation and application thereof

    CN115124564A

  • High-temperature-resistant flexible plugging material and preparation method thereof

    CN118344737A

  • Two-component, flexible and fast curing combination seal for sealing building constructions, roofs and repair of traffic areas

    EP2762545A1